UAE-HPLC-UV: New Contribution for Fast Determination of Total Isothiocyanates in Brassicaceae Vegetables. (6th December 2015) - Fusari, Cecilia M.; Locatelli, Daniela A.; Altamirano, Jorgelina C.; Camargo, Alejandra B.
Abstract : Total isothiocyanates content (ITC) is considered a good indicator of bioactive compounds responsible for beneficial effects related to Brassicaceae vegetables . Analytical performance is a critical factor for routine analysis in plant tissues. The extraction technique for isolating phytochemicals from Brassicaceae vegetables is currently the bottleneck of the methodology. The aim of this work was to optimize this step in the analytical process. Fast and less expensive alternative, based on ultrasound-assisted extraction technique (UAE) for direct extraction of GLS into an aqueous phase and further analysis of the hydrolysis product, was optimized. Full factorial (2 k ) design followed by Central Composite Design (CCD) was used to obtain the optimum extraction conditions. Selected conditions were homogenization time (9 min); ultrasound bath time (5 min); and sample-to-solvent ratio (1 : 5 w/v mg mL −1 ). The proposed analytical methodology exhibits satisfactory analytical performance in terms of linearity, precision (RSD < 2.4%), and limits of detection (26 nmol g −1  w.w.). The new analytical methodology was applied to cauliflower, cabbage, watercress, and broccoli samples with recoveries higher than 86%. The UAE extraction technique was showed to be efficient for real samples analysis leading to sensible, selective, and reproducible methodology for ITC analysis.